Ellie Haycock Is Totally Normal - Schreiber, Gretchen (New York : Wednesday Books, 2024)
Ellie, a high schooler with a rare genetic condition, navigates the divide between her "hospital-life" and "home-life," as a hospital stay brings her closer to Ryan, who challenges her perspective and makes her consider the extraordinary possibilities of her life.
new YA book 2024 spring.
Ages 12-18.
Keywords: Schools -- Fiction; Family life -- Fiction; Diseases -- Fiction; Friendship -- Fiction; High schools -- Fiction; Novels